For this question, we can assume that RS + ST = RT. So now, we just have to plug in the expressions for these lengths, and solve the equation.
(3x+1) + (2x-2) = 64
Because we are only dealing with one operation, the parentheses aren't necessary.
3x + 1 + 2x - 2 = 64
Next, we should combine like terms on the left side of the equation. We know that 3x + 2x = 5x, and that 1 - 2 = -1.
5x - 1 = 64
The goal of an equation is to get the variable alone. To do this, we have to get rid of the -1 on the left side of the equation. So, we are going to add 1 to both sides of the equation, to cancel out the -1 on the left side.
5x = 65
Finally, we are going to divide both sides by 5, as this is the inverse operation of multiplication, which is how the 5 and the x are connected.
x = 13
Therefore, the value of x is 13.